Ketidakpastian Hukum Dalam Kembalinya Tiktok Shop Sebagai Platform Social Commerce di Indonesia - Agustian Anhar, Dzacky; Kurniawan, Shelly (LPPM Universitas Ekasakti Padang, 2024)
TikTok Shop is a social commerce feature that allows users and creators to advertise and sell products through TikTok. Currently, TikTok is still not licensed as social commerce. As a platform that connects sellers and buyers, TikTok Shop has the responsibility to ensure the security and validity of transactions that occur in it. However, there are still some unresolved legal issues. This study aims to identify and analyze legal uncertainty related to the Minister of Trade Regulation Number 31 of 2023 concerning Business Licensing, Advertising, Guidance, and Supervision of Business Actors in Trading through Electronic Systems where social commerce must have a license first before it can operate in Indonesia, in this situation TikTok Shop cooperates with one of the largest e-commerce platforms (marketplace) in Indonesia, namely Tokopedia, which occurs in the return of TikTok Shop as a social commerce platform in Indonesia. The method used in this research is normative juridical. This research approach is a statutory approach (statue approach). Based on the results and discussion, it is found that there is legal uncertainty where TikTok Shop is not in accordance with the regulations mentioned above, especially regarding the rules stating that social commerce is not allowed to put a payment transaction feature (checkout) in it. It is hoped that the results of this study can contribute to increasing understanding and legal awareness for TikTok Shop users and provide recommendations for related parties to increase security and trust in transactions on this platform.